Representation of Racial Discrimination Dialog Through Discourse Analysis in the Film Maleficent: Mistress of Evil (2019) - Arifah Salsabila; Rahmaditya Khadifa Abdul Rozzaq Wijaya (Acceleration: Multidisciplinary Research Journal, 2024)
This study analyzes the representation of racial discrimination in the film Maleficent: Mistress of Evil (2019) through discourse analysis, focusing on how dialogues reflect systemic and everyday prejudices. The research employs a qualitative approach to examine instances of discrimination in the film’s narrative, particularly in the interactions between humans and the Fey. The findings reveal two primary forms of racial discrimination: chronic discrimination, which manifests through systemic oppression and historical marginalization, and daily discrimination, which appears in subtle prejudices and microaggressions. Queen Ingrith’s portrayal as a figure perpetuating anti-Fey sentiments underscores real-world parallels of racial bias, reinforcing stereotypes and societal divisions. The study highlights the film’s role in depicting discrimination as both a source of conflict and a reflection of broader societal tensions. By analysing these themes, this research contributes to discussions on racial representation in media and its implications for audiences’ perceptions of discrimination.